AplikasiRekayasa Nilai Untuk Evaluasi Produk Mesin Compos Mini Produksi - Abdul Aziz (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2010)
A product can look like a system, which is something that still has room for consideration of revisions (evaluation). In the evaluation, value engineering is one technique that systematically by using the techniques of identification of the functions required, apply the values and develop alternatives that achieve the best functional balance between cost and performance of a system or product. In compos Mini Machine products, value engineering done to the component cost is quite high (grade A on the ABC classification). Benefit Cost Ratio (BCR) is an important thing that needs to be calculated on the value engineering. The selected alternative for this article is the replacement of roofing material from metal plate to the plastic pulley with cost savings of 55%. Keywords: Value engineering, product evaluation, BCR